Upsetting of elastomeric material. The results of numerical and experimental investigations - Kut, Stanisław; Ryzińska, Grażyna; Niedziałek, Bernadetta (Advances in Mechanical and Materials Engineering)
This paper presents the results of research aimed at verifying the effectiveness of six selected models of elastomeric materials in which the constants were determined based on the uniaxial tension test. The effectiveness of the selected models (Neo-Hookean, Mooney with two and three constants, Signorini, Yeoh, Ogden) was determined based on a comparison between the results obtained in the experimental upsetting of an elastomeric cylinder and numerical FEM calculations for each model. Cyclic uniaxial tension testing of elastomer samples was employed to determine the stress-strain characteristic for the 18th load cycle. Material constant values were then calculated for each of the studied models based on this characteristic, with simulation of the upsetting process performed using the MARC/Mentat software program.